2003
DOI: 10.1007/s00417-003-0829-z
|View full text |Cite
|
Sign up to set email alerts
|

Iodide protection from UVB irradiation-induced degradation of hyaluronate and against UVB-damage of human conjunctival fibroblasts

Abstract: Iodide protects hyaluronate, a component of tear fluid and tissues of the anterior part of the eye, against UVB light-induced degradation. Also, injury of human conjunctival cells can be prevented by incubation with iodide before UVB irradiation. The mechanism of protection is likely to include an antioxidative reaction. To support the natural defence mechanisms of the eyes, the administration of an antioxidant such as iodide to artificial tears, for example, may help to prevent the damage of the eye provoked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
0
6
0
1
Order By: Relevance
“…The effect of UV irradiation on keratinocyte CD44 expression might be due either to a direct inhibitory effect of UV on CD44 gene transcription or to a presently unknown feedback mechanism in order to downregulate the amount of cell surface CD44 for HA already decreased in inter‐keratinocyte spaces. It has been shown that UVB degrades HA in cultured human conjunctival fibroblasts (33). Decrease of epidermal HA following UV irradiation might also be explained by degradation of free HA as a result of downregulation of keratinocyte CD44, which, under physiological conditions, binds and holds HA in interkeratinocyte spaces.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of UV irradiation on keratinocyte CD44 expression might be due either to a direct inhibitory effect of UV on CD44 gene transcription or to a presently unknown feedback mechanism in order to downregulate the amount of cell surface CD44 for HA already decreased in inter‐keratinocyte spaces. It has been shown that UVB degrades HA in cultured human conjunctival fibroblasts (33). Decrease of epidermal HA following UV irradiation might also be explained by degradation of free HA as a result of downregulation of keratinocyte CD44, which, under physiological conditions, binds and holds HA in interkeratinocyte spaces.…”
Section: Discussionmentioning
confidence: 99%
“…55 56 Iodide was shown to provide significant protection for hyaluronate, a component of tear fluid and tissues of the anterior part of the eye against ultraviolet B light induced oxidative degradation. 57 Also, injury to human conjunctival cells can be prevented by incubation with iodide before ultraviolet B irradiation. 57 Peroxidase activity, which can scavenge H 2 O 2 in the presence of a suitable substrate, has been detected in human tears.…”
Section: Discussionmentioning
confidence: 99%
“…57 Also, injury to human conjunctival cells can be prevented by incubation with iodide before ultraviolet B irradiation. 57 Peroxidase activity, which can scavenge H 2 O 2 in the presence of a suitable substrate, has been detected in human tears. 5 Iodide has been found to increase peroxidase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental influences (eg, air pollution, UV-B light) lead to oxidative reactions and consequently damage the tear film. 24 The increase in inflammatory activity may result in an increase in nerve excitation and therefore explain the highest sensitivity values in this subgroup.…”
Section: Cos and Etiology Of Dry Eyementioning
confidence: 99%